Conceptualizing clinical nurse leader practice: an interpretive synthesis. (5th February 2015) - Bender, Miriam
Abstract : Background: The Institute of Medicine's Future of Nursing report identifies the clinical nurse leader as an innovative new role for meeting higher health‐care quality standards. However, specific clinical nurse leader practices influencing documented quality outcomes remain unclear. Lack of practice clarity limits the ability to articulate, implement and measure clinical nurse leader‐specific practice and quality outcomes. Purpose and methods: Interpretive synthesis design and grounded theory analysis were used to develop a theoretical understanding of clinical nurse leader practice that can facilitate systematic and replicable implementation across health‐care settings. Results: The core phenomenon of clinical nurse leader practice is continuous clinical leadership, which involves four fundamental activities: facilitating effective ongoing communication; strengthening intra and interprofessional relationships; building and sustaining teams; and supporting staff engagement. Conclusion: Clinical nurse leaders continuously communicate and develop relationships within and across professions to promote and sustain information exchange, engagement, teamwork and effective care processes at the microsystem level. Implication for nursing management: Clinical nurse leader‐integrated care delivery systems highlight the benefits of nurse‐led models of care for transforming health‐care quality. Managers can use this study's findings to frame an implementation strategy that addresses theoretical domains of clinical nurse leader practice to help ensure practice success.